2018
DOI: 10.1039/c8ra03882a
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free base catalyzed intramolecular cyclization of 2-ynylphenols for efficient and facile synthesis of 2-substituted benzo[b]furans

Abstract: An efficient and practical transition-metal-free synthesis of 2-substituted benzo[b]furans catalyzed by readily accessible base was developed with broad substrates scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…The Sonogashira coupling of 9 with 1‐hexyne gave diyne 10 , and the subsequent removal of the acetyl groups with K 2 CO 3 and MeOH at 0 °C gave diol 11 in 22 % yield. In this deprotection step, the use of NaOH or hydrazine and/or reactions at room temperature resulted in lower yields of 11 due to the formation of the undesired benzofuran derivative through 5‐endo cyclization [22] . Similarly, diol 16 was synthesized in four steps from naphthalene‐2,6‐diol ( 12 ) via dibromide 13 , diacetate 14 , and diyne 15 under almost the same reaction conditions as the synthesis of diol 11 .…”
Section: Resultsmentioning
confidence: 99%
“…The Sonogashira coupling of 9 with 1‐hexyne gave diyne 10 , and the subsequent removal of the acetyl groups with K 2 CO 3 and MeOH at 0 °C gave diol 11 in 22 % yield. In this deprotection step, the use of NaOH or hydrazine and/or reactions at room temperature resulted in lower yields of 11 due to the formation of the undesired benzofuran derivative through 5‐endo cyclization [22] . Similarly, diol 16 was synthesized in four steps from naphthalene‐2,6‐diol ( 12 ) via dibromide 13 , diacetate 14 , and diyne 15 under almost the same reaction conditions as the synthesis of diol 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal-free, base-catalyzed intramolecular hydroalkoxylation of o-alkynyl phenols 18 was studied by Gao and co-workers for the rapid synthesis of benzofuran derivatives 19 in good yield (Scheme 10). [26] Various o-alkynyl phenols were treated with 10 mol% of Cs 2 CO 3 in CH 3 CN to furnish corresponding benzofuran derivatives. In general, it was observed that electron-rich aryl/aliphatic alkyne (R 2 = aryl ring with the electron-releasing group or alkyl) offered the corresponding furan in excellent yield.…”
Section: Base Catalyzed/promoted Intramolecular Hydroalkoxylationmentioning
confidence: 99%
“…CD intensity of 1 gradually decreased with time and disappeared after 72 h, while the half of that remained in 2 . o ‐Alkynyl phenol derivatives were known to form benzofuran rings under basic conditions [11] . For pyridine‐acetylene‐aniline structures, a similar decomposition to indole might occur slowly.…”
Section: Figurementioning
confidence: 99%